2007
DOI: 10.1007/s11242-007-9188-2
|View full text |Cite
|
Sign up to set email alerts
|

Grid Orientation Revisited: Near-well, Early-time Effects and Solution Coupling Methods

Abstract: The grid orientation effect is a phenomenon which leads to the computation of fundamentally different solutions on grids oriented diagonal and parallel to the principal flow direction. Grid orientation remains an important consideration for many practical simulation studies, and renewed interest in gas injection processes motivates the revisiting of this classical problem. In this article, we show that there are aspects of the grid orientation effect that can be traced back directly to the treatment of early-t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
10
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 27 publications
1
10
0
Order By: Relevance
“…The corresponding saturation field is shown in Figure 4.8 at t = 7.773, corresponding to roughly 0.19 pore volumes injected (PVI). This flow field is in good agreement with the results previously obtained by Kozdon, Gerritsen, and Christie [47] and Edwards [33]. …”
Section: D Quarter Five-spot Problemsupporting
confidence: 92%
See 2 more Smart Citations
“…The corresponding saturation field is shown in Figure 4.8 at t = 7.773, corresponding to roughly 0.19 pore volumes injected (PVI). This flow field is in good agreement with the results previously obtained by Kozdon, Gerritsen, and Christie [47] and Edwards [33]. …”
Section: D Quarter Five-spot Problemsupporting
confidence: 92%
“…Many such simulations involve adverse mobility ratio displacement; that is, the displacing fluid flows more easily through the porous medium than does the displaced fluid. For such cases, it has been demonstrated that numerical methods can suffer from fronts that are excessively smeared or that suffer from grid-orientation effects depending on whether flow is parallel or diagonal to mesh lines (see, for example, [47]). The grid-orientation phenomenon was first observed for immiscible displacement by Todd, O'Dell, and Hirasaki [78] in 1972.…”
Section: D Quarter Five-spot Problemmentioning
confidence: 99%
See 1 more Smart Citation
“…Since the resulting groundwater flow in the heated section was diagonal to the finite difference grid, grid orientation effects associated with upstream weighting of the advection terms were determined to be causing the excessive spreading of the tracer plumes (Kozdon et al, 2008). Consequently, the velocities obtained by the electro-thermal model were exported into a modified version of MT3DMS (Xheng, Wang, & Zheng, 1999).…”
Section: Voltage and Power Measurementsmentioning
confidence: 99%
“…In previous work, we have shown that extended injection well models reduce GOE by removing near-well perturbations that are critical in triggering unstable modes in the solution (Kozdon et al 2008). In this paper, we focus on the numerical scheme used for the transport equations.…”
mentioning
confidence: 99%